Pengembangan Sistem Deteksi Stres Berdasarkan Detak Jantung Pada Pengguna E-Learning - Muhammad Zulfikarrahman; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
E-Learning is instructions that are delivered through digital devices such as computer and mobile device that are provided to support learning. In the Faculty of Computer Science, Brawijaya University, e-learning has been used for learning activities. One of e-learning system that is being developed by Faculty of Computer Science is CodeManiac (CoMa). The exercises provided by CoMa is not adaptive to the mental condition of user. Stress has impact on the formation and retrieval of memories which have implication that stress can change the nature or quality of memories and can cause miss information. As a step to realizing an adaptable environment for CoMa, the first thing to do is to establish a physiological user monitoring system. Physiological signals can be used as features for user stress classification. Data from the monitoring system can be input for CoMa system as a basis for determining which exercise that will be given to user. The development process of system uses the waterfall method. The developed system produced 24 functional requirements and 2 non-functional requirements. Unit testing got 100% pass result and validation testing which have 33 test cases and got 100% pass result. Mobile application compatibility testing got result which is can run on Android Kitkat and Android Lollipop. Web application compatibility testing uses SortSite got no critical issue result. This system expected that can help CoMa for stress detection which can be used as a basis for determining exercise for users.